Women, makeup, and authenticity: Negotiating embodiment and discourses of beauty. (November 2020) - McCabe, Maryann; de Waal Malefyt, Timothy; Fabri, Antonella
This essay examines women's makeup practices and cultural tension between inner and outer constructs of beauty in the United States. Ethnographic research reveals competing discourses of beauty in the embodied experience of women, compared to images of beauty as promoted in advertising by the cosmetic industry. While the discourse of women's embodied experience emphasizes inner worth and connecting internal and external self, cosmetic advertising focuses on physical appearance and critical gaze of self and others. Women incorporate advertising discourses, not yielding to them or resisting them, but rather transforming them to suit their needs in using makeup products for creating confidence and preparing themselves for engagement in the world. At the same time, paradoxical adherence to advertising discourse indicates that gender inequality remains an ideological force in our society. Processes of ritualization produce and legitimize hierarchies of power in society. In this way, women's relationships to their bodies, commoditized products, and makeup practices are transformative as they are paradoxical.